Acute Myeloid Leukemia: Advancements in Diagnosis and Treatment - Meng-Ge Yu; Hu-Yong Zheng (Chinese Medical Journal, 2017)
Objective: Leukemia is the most common pediatric malignancy and a major cause of morbidity and mortality in children. Among all subtypes, a lack of consensus exists regarding the diagnosis and treatment of acute myeloid leukemia (AML). Patient survival rates have remained modest for the past three decades in AML. Recently, targeted therapy has emerged as a promising treatment. Data Sources: We searched the PubMed database for recently published research papers on diagnostic development, target therapy, and other novel therapies of AML. Clinical trial information was obtained from ClinicalTrials.gov. For the major purpose of this review that is to outline the latest therapeutic development of AML, we only listed the ongoing clinical trials for reference. However, the published results of complete clinical trials were also mentioned. Study Selection: This article reviewed the latest developments related to the diagnosis and treatment of AML. In the first portion, we provided some novel insights on the molecular basis of AML, as well as provided an update on the classification of AML. In the second portion, we summarized the results of research on potential molecular therapeutic agents including monoclonal antibodies, tyrosine kinase/Fms-like tyrosine kinase 3 (FLT3) inhibitors, epigenetic/demethylating agents, and cellular therapeutic agents. We will also highlight ongoing research and clinical trials in pediatric AML. Results: We described clonal evolution and how it changes our view on leukemogenesis, treatment responses, and disease relapse. Pediatric-specific genomic mapping was discussed with a novel diagnostic method highlighted. In the later portion of this review, we summarized the researches on potential molecular therapeutic agents including monoclonal antibodies, tyrosine kinase/FLT3 inhibitors, epigenetic/demethylating agents, and cellular therapeutic agents. Conclusion: Gene sequencing techniques should set the basis for next-generation diagnostic methods of AML, and target therapy should be the focus of future clinical research in the exploration of therapeutic possibilities.